Quantitative evaluation of tailoring within SPICE‐compliant security‐informed safety‐oriented process lines. Issue 3 (16th August 2019) - Gallina, Barbara
Abstract: In the context of SPICE‐compliant and (security‐informed) safety processes, efficient process tailoring is necessary due to the increasing proliferation of requirements, which, if not systematised, may become an unmanageable cognitive overload leading to process degradation instead of improvement. Recently, security‐informed safety‐oriented process line engineering (SiSoPLE) has been proposed as a sound solution to systematise common and variable process elements in the context of security‐informed safety‐oriented processes described within security as well as safety‐related standards. SiSoPLE represents an extension of safety‐oriented process line engineering (SoPLE). The gain of the application of SoPLE in terms of efficient tailoring via reuse was measured in a previous work, where the GQM + Strategies model, an extension of the goal/question/metric (GQM) paradigm, was adopted to develop a measurement model for achieving quantitative evidence. In this paper, we develop further our previously proposed measurement model to achieve quantitative evidence regarding the benefits of using process line engineering extended to SPICE‐compliant security‐informed safety processes. We then apply our extended GQM + Strategies model on a SPICE for space‐compliant SiSoPL to illustrate and assess its usefulness. Finally, we discuss our findings and provide our perspectives on quantitative evaluation of tailoring in the context of critical‐systems engineering.